2021
DOI: 10.1002/ptr.7217
|View full text |Cite
|
Sign up to set email alerts
|

The effect of red pepper/capsaicin on blood pressure and heart rate: A systematic review and meta‐analysis of clinical trials

Abstract: Several studies have assessed the effect of red pepper on blood pressure (BP) and heart rate (HR) and reported controversial results. The aim of this study was to perform a systematic review and meta-analysis of clinical trials that evaluated the effect of red pepper/capsaicin consumption on BP and HR. Medline, Scopus, Cochrane Library, and Google Scholar were systematically searched, from database inception to August 2020, to ascertain clinical trials that evaluated the effects of red pepper or capsaicin on s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 38 publications
1
9
0
1
Order By: Relevance
“…[ 23 ] The consumption of spicy food is associated with a 12% lower risk of all‐cause mortality in Table 2 (HR/RR = 0.88, 95% CI, 0.86–0.90; I 2 = 0%). [ 24 ]…”
Section: Resultsmentioning
confidence: 99%
“…[ 23 ] The consumption of spicy food is associated with a 12% lower risk of all‐cause mortality in Table 2 (HR/RR = 0.88, 95% CI, 0.86–0.90; I 2 = 0%). [ 24 ]…”
Section: Resultsmentioning
confidence: 99%
“…The effects of capsaicin and red peppers on cardiovascular responses are currently controversial due to the vast heterogeneity between protocols and doses used in previous literature ( Shirani et al, 2021 ). However, recent research has shown that supplementation with purified capsaicin does not alter heart rate during an incremental exercise test in a cycloergometer until exhaustion ( Giuriato et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the association between spicy food and hypertension, results from previous studies are also con icting. Meta-analysis of clinical trials [23] showed no signi cant effect of red pepper/capsaicin on blood pressure (BP).…”
Section: Introductionmentioning
confidence: 99%